Presentation of valid correlations in some morphological variables and basic and specific motor skills in young people aged 13-14 years engaged in basketball - Miftari, Florian; Salihu, Hazir; Selimi, Musa (Journal of Education, Health and Sport, 2018)
Study-research deals with younger students of both sexes aged 13-14, who, besides attending classes of physical education and sports, also practice in basketball schools in the city of Pristina. The experiment contains a total of 7 morphological variables, while four tests of basic motion skills and seven variables are from specific motion skills. In this study, the verification and analysis of the correlation of morphological characteristics and basic and situational motor skills in both groups of both sexes (boys and girls) were treated. Based on the results obtained between several variables, valid correlations with high coefficients are presented, whereas among the variables are presented correlations with optimal values. The experimentation in question includes the number of 80 entities of both sexes; the group of 40 boys and the other group consisting of 40 girls who have undergone the tests for this study-experiment.